2019
DOI: 10.1001/jamapsychiatry.2018.3252
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hippocampal Glutamate Levels With Adverse Outcomes in Individuals at Clinical High Risk for Psychosis

Abstract: IMPORTANCE Preclinical and human data suggest that hippocampal dysfunction plays a critical role in the onset of psychosis. Neural hyperactivity in the hippocampus is thought to drive an increase in subcortical dopamine function through glutamatergic projections to the striatum. OBJECTIVE To examine the association between hippocampal glutamate levels in individuals at clinical high risk for psychosis and their subsequent clinical outcomes. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study of 86 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 54 publications
4
85
0
Order By: Relevance
“…30 A GAF score of 65 was chosen for consistency with the score in previous neuroimaging studies in CHR. 41,42 Binary logistic regression analyses were performed (transition vs nontransition; good vs poor functioning) with the same covariates. After preprocessing, segmented, normalized, and smoothed GMV images were analyzed in a group using SPM12 to find the associations with DFAR task performance.…”
Section: Dfar Data and Data Integrationmentioning
confidence: 99%
“…30 A GAF score of 65 was chosen for consistency with the score in previous neuroimaging studies in CHR. 41,42 Binary logistic regression analyses were performed (transition vs nontransition; good vs poor functioning) with the same covariates. After preprocessing, segmented, normalized, and smoothed GMV images were analyzed in a group using SPM12 to find the associations with DFAR task performance.…”
Section: Dfar Data and Data Integrationmentioning
confidence: 99%
“…Using this technique, numerous (but not all (Merritt et al, 2016)) studies have reported alterations in glutamate (and/or glutamate plus glutamine (Glx)) levels in people at high risk of psychosis vs controls, particularly in the hippocampus (Bloemen et al, 2011;Shakory et al, 2018), frontal (Merritt et al, 2016) or anterior cingulate cortex (ACC) Tibbo et al, 2004) and thalamus . Moreover, within CHR-P samples, altered metabolite levels at baseline appear related to clinical outcomes; thalamic glutamate is lower at baseline in those who do not remit by follow up (Egerton et al, 2014), and baseline hippocampal glutamate is elevated in those who transition (vs those who do not), and in those with poor (vs good) functional outcomes (Bossong et al, 2018). There is also evidence that neurochemical alterations in CHR-P are not restricted to glutamate or Glx; higher levels of hippocampal myo-inositol at first presentation have been reported in CHR-P patients with poor functional and clinical outcomes (with effect sizes surpassing that of glutamate), which suggests that hippocampal integrity may be compromised more generally (Bossong et al, 2018).…”
Section: <Figure 1>mentioning
confidence: 99%
“…Moreover, within CHR-P samples, altered metabolite levels at baseline appear related to clinical outcomes; thalamic glutamate is lower at baseline in those who do not remit by follow up (Egerton et al, 2014), and baseline hippocampal glutamate is elevated in those who transition (vs those who do not), and in those with poor (vs good) functional outcomes (Bossong et al, 2018). There is also evidence that neurochemical alterations in CHR-P are not restricted to glutamate or Glx; higher levels of hippocampal myo-inositol at first presentation have been reported in CHR-P patients with poor functional and clinical outcomes (with effect sizes surpassing that of glutamate), which suggests that hippocampal integrity may be compromised more generally (Bossong et al, 2018). Metabolite alterations have also been observed in other brain regions in CHR-P and other (i.e.…”
Section: <Figure 1>mentioning
confidence: 99%
“…While single voxel spectroscopic measurements might be considered the Gold Standard in terms of reliability of data, evolving metabolic mapping techniques provide opportunities for evaluating the metabolic state of the entire brain. Our focus on artefact control, partial volume correction, QA filtration, and data aggregation from multiple subjects has permitted mapping of metabolite ratios metabolites such as tNAA, Glx and tCho at deeper regions of the brain adjacent to the ventricles; areas of interest for studying metabolic alterations linked to psychiatric disorders [27,47].…”
Section: Discussionmentioning
confidence: 99%
“…Two adjacent 10mm MRSI slices (20mm slab) were acquired axially to intersect deep GM nuclei located adjacent to the ventricles while maximizing the amount of tissue acquired through the occipital lobe. This region is of interest since many MRSI studies performed at UHF thus far have focused primarily on brain regions above the ventricles, whereas neuropsychiatric disorders (schizophrenia or psychosis, but also obsessive compulsive disorder) are believed to have origins, at least partly, in deep gray matter structures [27].…”
Section: Mrsi Data Acquisitionmentioning
confidence: 99%